A Novel Mineral Composition Increases Soybean Crop Yield by Mitigating Stress Induced by Ultraviolet-A and -B Radiation - Abreu, André L.; Gratão, Priscila L. [UNESP]; Rodriguez, Carlos A. V.; Sousa Junior, Gilmar S. (MDPI, 2023)
Ultraviolet radiation (UVR) is an important environmental abiotic stress that consistently affects the yield potential of agricultural crops causing hidden yield losses; few practical solutions are available for protecting large-scale field cultivation. Here, we assess the protective effect of a novel mineral composition principally based upon a concentrated suspension of microparticles of crystalline and insoluble quartz sand applied as foliar spray over the top of plants to mitigate the stress effects of UV-A or UV-B radiation. Soybean (Glycine max (L.) Merrill) plants were cultivated under three alternative UVR exposure scenarios (no UV, +UV-A, +UV-B) to compare sprayed and unsprayed plants. Measurements of malondialdehyde (MDA) and proline contents demonstrated the effects of +UV-A and +UV-B on plants and the effectiveness of the foliar spray in mitigating such stress. Biometric assessment showed that root weight, foliar biomass and number of pods of unsprayed plants were negatively impacted by both +UV-A and +UV-B; whereas, in sprayed plants, the damages for both +UV-A and +UV-B were almost entirely mitigated. The results of this study endorse the use of quartz sand microparticles as a promising tool for growers to achieve sustainable yields in soybeans and potentially other field crops in the face of increasing challenges due to climate change.
Keywords: abiotic stress; climate change; quartz sand; soybeans; UV radiation